Reform of mental health services in Eastern Europe and former Soviet republics: progress and challenges since 2005. (16th April 2018) - Muijen, Matt; McCulloch, Andrew
Abstract : For over a decade, concerted efforts have been made in Europe to reform mental health services and move away from institutions to community-based models of care, supported by international policy statements, good practice examples and research evidence. Progress has been uneven. So what is the status of mental healthcare across the World Health Organization European Region, and what factors support, or detract from, such progress?